Buchholzia coriacea Leaves Attenuated Dyslipidemia and Oxidative Stress in Hyperlipidemic Rats and Its Potential Targets In Silico - Daniel E. Uti; Udu A. Ibiam; Wilson A. Omang; Precious A. Udeozor; Grace U. Umoru; Solomon K. Nwadum; Inalegwu Bawa; Esther U. Alum; Joseph C. Mordi; Edith O. Okoro; Uket Nta Obeten; Eucharia N. Onwe; et al. (Pharmaceutical Fronts, 2023)
The study aimed to investigate how the solvent extract of Buchholzia coriacea (BCE), a widely known hypolipidemic agent, could contribute to hyperlipidemia treatment and identify the potential bioactive compounds. We studied Wistar albino rats, dividing them into seven groups: the normal control, normal rats treated with 400 mg/kg.b.wt of BCE (NRG group), the hyperlipidemic control (HPC group), hyperlipidemic rats treated with atorvastatin, a standard control drug (SC group), as well as 200, 400, and 800 mg/kg.b.wt of BCE extract respectively (T1, T2, T3 groups). The potential compounds that functioned in BCE extract were analyzed by in silico binding to acetyl-CoA carboxylase (ACC) and fatty acid synthase (FASN). The binding affinities and drug-like properties of the compounds were determined using virtual screening and absorption distribution metabolism excretion and toxicity prediction analysis. The gas chromatography-mass spectrometry analysis identified alkaloids, saponins, flavonoids, phenols, terpenoids, and 44 chemical compounds in the leaf extract of BCE. BCE significantly reduced the levels of triacylglycerol, total cholesterol, low-density lipoprotein, very low-density lipoprotein, atherogenic coefficient, atherogenic index, and coronary risk index, while enhancing the levels of high-density lipoprotein and cardioprotective index in comparison to the HPC group. The BCE reduced malondialdehyde quantities, which exhibit high levels in HPC. Superoxide dismutase and glutathione peroxidase activities as well as glutathione levels, which are otherwise reduced in HPC, were increased upon the BCE treatment. Among the identified BCE compounds, lupenone and 2,7-dimethylnaphthalene exhibited the highest binding affinities to ACC and FASN, suggesting that these two compounds might be the bioactive BCE components displaying hypolipidemic properties. BCE is found to be beneficial in blocking hyperlipidemia through the modulation of lipid profile, the protection of cardiovascular function, as well as the suppression of oxidative stress. BCE may be a natural source for exploring novel drugs for the treatment of dyslipidemia.